A Voice of Their Own Encouraging Caring and Ethical Practices in Trauma Screen Translation - Bosseaux, Charlotte; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
This open access book explores which audiovisual translation methods or techniques are the most ethical when translating personal narratives dealing with trauma and emotions, and provides good practice guidelines for different stakeholders (audiovisual translators, Language Service Providers, charities, survivors and filmmakers) to ensure that the voices of those who have suffered from trauma and Gender-Based Violence are ethically conveyed on-screen. It also shows how subtitlers cope with the translation of challenging sensitive material. The work described in this book is based on Prof Bosseaux$1 (Bs Ethical Translation project and is underpinned by a practical component: a multilingual documentary featuring women who have gone through traumatic events and whose first language is not English. Above all, the research emphasises the importance of filming and translating ethically with a focus on making sure survivors and audiovisual translators$1 (Bvoices are fully heard through respectful translation. This book showcases the theories and methods used and developed throughout the Ethical Translation project and the results of the research conducted, ultimately demonstrating the importance of carrying out practice-based research and encouraging collaboration between academics, practitioners and stakeholders to produce research that can be of use to, and be applied by, these groups. Professor Charlotte Bosseaux holds a chair in Audiovisual Translation Studies at the University of Edinburgh. Her research on voice in translation spans different fields including literary translation (e.g., How does it Feel: Point of View in Translation, 2007) and audiovisual translation (e.g., Dubbing, Film and Performance: Uncanny Encounters, 2015). Prof Bosseaux currently writes on documentaries examining how the voices of survivors of Gender-Based Violence and trauma are translated in this context (2020 and AHRC Project 2022-2023: The Ethical Demands of Translating Gender-Based Violence: a Practice-Based Research Project). Other publications include work on Marilyn Monroe (2012 and 2012a), Julianne Moore (2019), Buffy the Vampire Slayer (2008 and 2014), multilingualism in TV series (2023), music (2011, forthcoming 2025) and crime fiction in translation (2018).s
Chapter 1 Introduction -- Chapter 2 Ethics and the Translation of Trauma, Gender-Based Violence and Emotions -- Chapter 3 Documentary Translation -- Chapter 4 Methodological Framework -- Chapter 5 Surviving Translation -- Chapter 6 Conclusion.
Keywords: Motion pictures; Documentary films; Translating and interpreting; Audio-Visual Culture; Documentary Studies; Language Translation